Tax Reform and Its Impact on Gender Equality in the Workforce - Suryani, Wina (Manunggal Halim Jaya, 2024)
This qualitative research investigates the nexus between tax reform and gender equality in the workforce, aiming to provide insights into the impact of tax policies on labor market dynamics and gender disparities. Employing a systematic literature review methodology, diverse scholarly sources from economics, sociology, gender studies, and public policy are analyzed to discern patterns, themes, and relationships within the data. The study examines the differential effects of tax reforms on men and women, highlighting disparities in labor force participation, earnings distribution, and economic empowerment. Findings suggest that tax policies intersect with broader socio-economic inequalities, magnifying disparities experienced by marginalized groups, particularly women of color and immigrant women. However, the research also identifies opportunities for promoting gender equality through targeted tax incentives, progressive taxation schemes, and gender-responsive public finance measures. The study underscores the importance of adopting intersectional approaches to tax reform and integrating gender perspectives into policy design, implementation, and evaluation processes to foster greater inclusivity and equity within tax systems.